2003
DOI: 10.1086/375266
|View full text |Cite
|
Sign up to set email alerts
|

Decline of the Space Density of Quasars betweenz= 2 andz= 4

Abstract: We define a new complete sample of 13 optically-luminous radio quasars (M AB (1450Å)< −26.m 9 and log P 1.4GHz (W Hz −1 ) > 25.7) with redshift 3.8 < z < 4.5, obtained by crosscorrelating the FIRST radio survey and the APM catalogue of POSS-I. We measure the space density to be (1.0 ± 0.3) Gpc −3 , a factor 1.9±0.7 smaller than the space density of similar quasars at z ≈ 2 (FBQS). Using a new measurement of the radio-loud fraction of quasars we find that at z = 4 the total space density of quasars with M AB (1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
41
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(56 citation statements)
references
References 43 publications
15
41
0
Order By: Relevance
“…A better global fit was achieved allowing z top to vary with luminosity as z top,0 and δ z top being free parameters. The fit gave positive values for both of them, consistent with earlier indications that the high‐ z decline of the space density is more pronounced and starts at lower redshifts for less powerful sources (Hook, Shaver & McMahon 1998; Waddington et al 2001; Vigotti et al 2003; Cirasuolo, Magliocchetti & Celotti 2005; Cirasuolo et al 2006). The luminosity dependence of the high‐ z decline is qualitatively similar to the downsizing observed for galaxies and optically and X‐ray selected quasars (Cowie et al 1996; Barger et al 2005; Pérez‐González et al 2008).…”
Section: Agn‐powered Sourcessupporting
confidence: 87%
“…A better global fit was achieved allowing z top to vary with luminosity as z top,0 and δ z top being free parameters. The fit gave positive values for both of them, consistent with earlier indications that the high‐ z decline of the space density is more pronounced and starts at lower redshifts for less powerful sources (Hook, Shaver & McMahon 1998; Waddington et al 2001; Vigotti et al 2003; Cirasuolo, Magliocchetti & Celotti 2005; Cirasuolo et al 2006). The luminosity dependence of the high‐ z decline is qualitatively similar to the downsizing observed for galaxies and optically and X‐ray selected quasars (Cowie et al 1996; Barger et al 2005; Pérez‐González et al 2008).…”
Section: Agn‐powered Sourcessupporting
confidence: 87%
“…The 5 GHz luminosity functions, computed using the full 1 Jy sample, while confirming that the radio luminosity density peaks at z peak 2.5 (Dunlop & Peacock 1990;Shaver et al 1996Shaver et al , 1999 do not provide evidence for deviations from pure luminosity evolution, reported by other analyses (Hook et al 1998;Vigotti et al 2003), perhaps due to the poor statistics. In particular we notice that the derived epoch-dependent 5 GHz luminosity function is fairly well represented by the model by De Zotti et al (2005).…”
Section: Discussionsupporting
confidence: 69%
“…At lower frequencies the steep‐spectrum sources dominate the population at all luminosities and only contain the rare extremely luminous flat‐spectrum sources. Since it is the flat‐spectrum population that has a high quasar identification rate, this is the sample used to investigate evolution of flat‐spectrum quasars (Dunlop & Peacock 1990; Shaver et al 1996; Jarvis & Rawlings 2000; Vigotti et al 2003; Wall et al 2005). Our frequency selection provides a much larger fraction of these sources without introducing a different class of sources; thus, we reduce the bias by having a high‐frequency‐selected sample (e.g.…”
Section: The Redshift Cut‐off and The Effect Of Spectral Curvaturementioning
confidence: 99%
“…The space density has been shown to decline beyond the redshift of 3 in flat‐spectrum radio sources (e.g. Peacock 1985; Dunlop & Peacock 1990; Shaver et al 1996; Wall et al 2005), X‐ray‐selected quasars (Hasinger, Miyaji & Schmidt 2005) and optically selected quasars (Schmidt, Schneider & Gunn 1991; Vigotti et al 2003). The details of whether such an evolution is purely due to space density evolution or due to luminosity evolution is yet to be resolved.…”
Section: Introductionmentioning
confidence: 99%